Meaning-Making and Political Campaign Advertising : A Cognitive-Linguistic and Film-Analytical Perspective on Audiovisual Figurativity - Horst, Dorothea (Cinepoetics - English edition ;, 2018)
Although recent linguistic and media-studies' research has increasingly dealt with forms of imagery beyond language, such as in audiovisual formats, only little attention has been paid to the specific media character of audiovisual images. This raises a theoretical as well as methodological problem: How can processes of figurative meaning making in audiovisual media be adequately conceptualized and described? The book intends to bridge this research gap with an analysis of campaign commercials, a hitherto largely underexplored object of study in metaphor and metonymy research. To achieve this goal, a transdisciplinary film-analytical and cognitive-linguistic account of audiovisual figurativity is developed and examined through a comparative analysis of figurative meaning-making processes in German and Polish campaign commercials from 2009 and 2011. By setting the inseparable intertwining of language and cinematic staging, sensing and understanding center stage, the book provides insight into the dynamic nature and embodied affective grounds of audiovisual figurativity, and challenges the long-known dichotomies of rational discourse and affective manipulation, political message and media effect.